TESTING THE IMPACT OF TAX PLANNING, TAX AVOIDANCE AND CAPITAL STRUCTURE ON COMPANY VALUE DURING THE COVID-19 PANDEMIC - Lulu Nailufaroh; Herman Wijaya (Jurnal Ekonomi, 2022)
Since the beginning of 2020, the condition of the global and domestic capital markets has been severely affected by the coronavirus disease pandemic. The current investment climate conditions have been affected due to the coronavirus disease pandemic. The Covid-19 pandemic has also negatively impacted the company, such as a decrease in stock prices and financial performance, which could affect the company's value. The firm value is the investor's perception of the company's success rate that is clearly visible in relation to the stock price. If the stock price is high, it automatically causes the company's value to be high. This study aims to test and analyze the factors influencing the company's value during the Covid-19 pandemic in the Food and Beverage Sub-Sector Manufacturing company in 2019-2021. The collected research data will be processed using multiple regression analysis techniques with purposive sampling. The results showed that: (1) tax planning has a positive and significant effect on the value of the company, (2) tax avoidance does not affect the value of the company, and (3) The capital structure does not affect the value of the company